Composite diaphragm, preparation method thereof and lithium battery

By using a composite coating containing a high specific surface area solid electrolyte and a hydrophobic agent on the lithium battery separator, the problem that the lithium battery separator is prone to short circuit and fire at high temperatures is solved, achieving high liquid retention rate and low moisture effect, and improving the battery's durability cycle life and safety performance.

CN119340614APending Publication Date: 2025-01-21HUZHOU NANMU-NANO SCI & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411341340.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing lithium battery separators are prone to shrinkage and deformation at high temperatures, resulting in the risk of short circuit and fire explosion. In addition, traditional coating materials do not improve ionic conductivity, which has the contradiction between high liquid retention rate and low moisture effect.

Method used

Using a composite diaphragm, its coating contains solid electrolyte, thickening agent, hydrophobe, dispersant and binding agent. The ratio of solid electrolyte is 20m2/g ~ 100m2/g. Potassium siliconate, through specific component proportions and preparation methods, achieve high -fidelity liquid rate and low moisture effect.

Benefits of technology

It improves the cycle life and safety of lithium batteries, enhances the mechanical properties of the separator and the retention capacity of the electrolyte, and reduces the impact of moisture on the performance of the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340614A_ABST
    Figure CN119340614A_ABST
Patent Text Reader

Abstract

The invention discloses a composite diaphragm, a preparation method thereof and a lithium battery. The composite diaphragm comprises a base diaphragm, the coating is arranged on at least one side of the base film in the thickness direction, and the coating comprises a solid electrolyte, a thickening agent, a water repellent agent, a dispersing agent and a binding agent; wherein the specific surface area of the solid electrolyte is 20 m < 2 > / g to 100 m < 2 > / g, and the water repellent agent is selected from at least one of sodium methyl silicate and potassium methyl silicate. In the coating of the composite diaphragm provided by the invention, the solid electrolyte has a specific surface area of 20 m < 2 > / g-100 m < 2 > / g, the water repellent agent is selected from at least one of sodium methyl silicate and potassium methyl silicate, the solid electrolyte has extremely high adsorption capacity to liquid or gas, and meanwhile, the water repellent agent enables the composite diaphragm to have high liquid retention and reduce adsorption to moisture at the same time; further, the influence of moisture on the composite diaphragm and battery performance is reduced, and the service life and safety performance of the composite diaphragm and even the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a composite diaphragm and a preparation method thereof, and a lithium battery. Background Art

[0002] In the structure of lithium batteries, the diaphragm is one of the key internal components. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery. The main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. Different types of batteries use different diaphragms. For lithium battery series, since the electrolyte is an organic solvent system, a diaphragm material that is resistant to organic solvents is required, and a high-strength thin-film polyolefin porous membrane is generally used.

[0003] Traditional polyolefin separators have poor heat resistance. At temperatures above 150°C, the separators will shrink and deform, causing short circuits in the battery, which may lead to fire and explosion of the battery, affecting the driving safety of electric vehicles. Existing lithium battery separator coatings are mainly made of materials such as aluminum oxide, boehmite, and magnesium hydroxide to make coating slurries. The slurry is coated on the separator and dried to form a ceramic coating mainly composed of materials such as aluminum oxide, boehmite, and magnesium hydroxide, so as to improve the thermal stability of the separator, the wettability of the electrolyte, and improve the battery performance. However, these coating materials themselves do not have ionic conductivity, so these coatings do not improve the ionic conductivity of the separator.

[0004] The existing technology uses a polymer additive of polysilazane to greatly reduce the moisture after film formation, and at the same time greatly reduce the mechanical strength of the diaphragm. However, there is a problem with this technology in application. The oily polysilazane is unevenly dispersed in the aqueous slurry, and a large amount of dispersant is required to assist its distribution in the aqueous slurry. Generally, high BET solid electrolytes have a strong adsorption capacity for liquids or gases. In view of this, they are usually applied to diaphragms to achieve the storage capacity of electrolytes, but the finished diaphragms will also be environmentally unstable and will absorb moisture in the air and bring it into the battery, affecting the electrical performance of the battery. Summary of the invention

[0005] The technical problem to be solved by the embodiments of the present invention is to provide a composite diaphragm and a preparation method thereof and a lithium battery, which can solve the contradiction between high liquid retention rate and low water content and improve the cycle life and safety of the battery.

[0006] In order to solve the above technical problems, the present invention provides a composite diaphragm, which comprises: a base film; a coating, wherein the coating is arranged on at least one side of the base film in the thickness direction, and the coating comprises a solid electrolyte, a thickener, a hydrophobic agent, a dispersant and a binder; wherein the specific surface area of ​​the solid electrolyte is 20m 2 / g~100m 2 / g, the hydrophobic agent is selected from at least one of sodium methyl silicate and potassium methyl silicate.

[0007] In a feasible implementation, the mass ratio of the solid electrolyte, thickener, hydrophobic agent, dispersant and binder in the coating is (75-85): (1-8): (1-5): (1-8): (1-10).

[0008] In a feasible implementation, the particle size D50 of the solid electrolyte is 0.3-8 μm, the thickness of the base film is 1-15 μm, and the thickness of the coating is 1-10 μm.

[0009] In a feasible implementation, the thickener is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, sodium carboxymethyl cellulose, methyl cellulose and sucrose.

[0010] In a feasible implementation, the dispersant is selected from one or more of sodium silicate, sodium hexametaphosphate, sodium stearate, fatty alcohol polyoxyethylene ether, polyacrylamine and polyvinyl alcohol.

[0011] In a feasible implementation, the binder is selected from one or more of polystyrene-butadiene rubber, vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, polyimide, polyvinyl pyrrolidone, and an emulsion or solution with polyethylene oxide as the solute.

[0012] Correspondingly, the present invention also provides a method for preparing a composite diaphragm, which comprises the following steps: obtaining a base film, adding a thickener to water, stirring evenly, and obtaining a first mixed liquid; adding a solid electrolyte to the first mixed liquid, stirring evenly, and obtaining a second mixed liquid; adding a hydrophobic agent and a dispersant to the second mixed liquid, stirring evenly, and obtaining a third mixed liquid; adding a binder to the third mixed liquid, stirring evenly, and obtaining a target slurry, and applying the target slurry to at least one side of the base film to obtain a precursor composite diaphragm; curing the precursor diaphragm to obtain a target composite diaphragm.

[0013] In a feasible implementation, the ratio of water in the second mixed liquid to the solid electrolyte is: (2-4):1.

[0014] In a feasible implementation, the operation of curing the precursor membrane is drying and curing, the drying and curing temperature is 90-150° C., and the drying and curing time is 10-60 min.

[0015] Correspondingly, the present invention also provides a lithium battery, comprising any one of the composite separators described above.

[0016] The implementation of the present invention has the following beneficial effects:

[0017] In the coating of the composite diaphragm provided in the present application, the solid electrolyte has 20m 2 / g~100m 2 / g of specific surface area, and has a strong adsorption capacity for liquid or gas, so the composite diaphragm has a good effect of retaining electrolyte. At the same time, the hydrophobic agent enables the composite diaphragm to reduce the adsorption of water while having high liquid retention, achieve low moisture, and further reduce the influence of moisture on the composite diaphragm and battery performance. In addition, the hydrophobic agent is selected from at least one of sodium methyl silicate and potassium methyl silicate. These two hydrophobic agents have good water solubility and good dispersion effect during the preparation process. The hydrophobic agent of the composite diaphragm finally prepared is evenly dispersed, so it has a better hydrophobic effect, achieves a better low moisture effect, further reduces the mechanical performance defects caused by water absorption of the composite diaphragm, and improves the service life and safety performance of the composite diaphragm and even the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a comparison chart of the hydrophobicity of the diaphragms prepared in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0021] The present application provides a composite membrane in one aspect. The composite membrane includes: a base membrane and a coating. The coating is disposed on at least one side of the base membrane in the thickness direction. The coating includes a solid electrolyte, a thickener, a hydrophobic agent, a dispersant, and a binder. The specific surface area of ​​the solid electrolyte is 20 m 2 / g~100m 2 / g, the hydrophobic agent is selected from at least one of sodium methyl silicate and potassium methyl silicate. In the coating of the composite diaphragm provided in the present application, the solid electrolyte has 20m 2 / g~100m 2 / g of specific surface area, and has a strong adsorption capacity for liquid or gas, so the composite diaphragm has a good effect of retaining electrolyte. At the same time, the hydrophobic agent enables the composite diaphragm to reduce the adsorption of water while having high liquid retention, achieve low moisture, and further reduce the influence of moisture on the composite diaphragm and battery performance. In addition, the hydrophobic agent is selected from at least one of sodium methyl silicate and potassium methyl silicate. These two hydrophobic agents have good water solubility and good dispersion effect during the preparation process. The hydrophobic agent of the composite diaphragm finally prepared is evenly dispersed, so it has a better hydrophobic effect, achieves a better low moisture effect, further reduces the mechanical performance defects caused by water absorption of the composite diaphragm, and improves the service life and safety performance of the composite diaphragm and even the battery.

[0022] Optionally or preferably, the solid electrolyte has a BET of 80 m 2 / g~100m 2 / g. In this way, the balance between high liquid retention and low moisture effects of the composite diaphragm can be further coordinated to achieve the best high liquid retention and low moisture effects, further reduce the mechanical performance defects caused by water absorption of the composite diaphragm, and improve the service life and safety performance of the composite diaphragm and even the battery.

[0023] In a feasible implementation, the particle size D50 of the solid electrolyte is 0.3 μm to 8 μm.

[0024] In a feasible embodiment, the thickness of the base film is 1 to 15 μm, and the thickness of the coating is 1 to 10 μm. In a feasible embodiment, the base film can be a PE, PP, PAN or PVDF base film. Optionally or preferably, the base film is a PE base film. The PE base film has good insulation properties, is odorless, non-toxic, environmentally friendly, corrosion-resistant, and has a long service life. Using the PE base film as the base film of the composite diaphragm is conducive to improving the service life of the composite diaphragm and is also conducive to a wide range of applications.

[0025] In a feasible embodiment, the mass ratio of the solid electrolyte, thickener, hydrophobic agent, dispersant and binder in the coating of the composite diaphragm is (75-85): (1-8): (1-5): (1-8): (1-10). Such a mass ratio of the solid electrolyte, thickener, hydrophobic agent, dispersant and binder can further coordinate the balance between the high liquid retention and low moisture effects of the composite diaphragm, achieve the best high liquid retention and low moisture effects, further reduce the mechanical performance defects caused by the water absorption of the composite diaphragm, and improve the service life and safety performance of the composite diaphragm and even the battery.

[0026] In a feasible embodiment, the thickener is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, sodium carboxymethyl cellulose, methyl cellulose and sucrose. Optionally or preferably, the thickener is sodium carboxymethyl cellulose. Sodium carboxymethyl cellulose has good thermal stability and pH stability, and can maintain its thickening effect even under different temperatures and acid-base environments. In addition to thickening, sodium carboxymethyl cellulose can also be used as an emulsifier and stabilizer to prevent stratification and precipitation. Sodium carboxymethyl cellulose can absorb and retain moisture. Sodium carboxymethyl cellulose has good compatibility with additives and ingredients, and can be used in combination with solid electrolytes, hydrophobic agents, dispersants and binders to achieve optimal results.

[0027] In a feasible embodiment, the dispersant is selected from one or more of sodium silicate, sodium hexametaphosphate, sodium stearate, fatty alcohol polyoxyethylene ether, polyacrylamine and polyvinyl alcohol. Optionally or preferably, the dispersant is polyacrylamine. Polyacrylamide can prevent solid particles from aggregating and precipitating in a suspension, maintain the uniform dispersion of particles, and thus improve the stability of the system. By adjusting the molecular weight and charge density of polyacrylamide, polyacrylamide can change the viscosity and flow characteristics of the fluid, making it more suitable for specific application requirements. The long chain structure of polyacrylamide can be adsorbed on the surface of the particles and form a protective film to prevent direct contact between particles, effectively prevent agglomeration, and ensure a good dispersion effect. Compared with some traditional dispersants, polyacrylamide is generally considered to be a safer and more environmentally friendly option because it is biodegradable and less toxic. Polyacrylamide can work in different pH ranges. Due to the efficient dispersibility of polyacrylamide, polyacrylamide often only needs a small amount to achieve the desired effect, which can reduce the overall cost of use.

[0028] In a feasible embodiment, the binder is selected from one or more of an emulsion or solution with polystyrene butadiene rubber, vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, polyimide, polyvinyl pyrrolidone, and polyethylene oxide as a solute. Optionally or preferably, the binder is selected from a solution with polystyrene butadiene rubber, vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, polyimide, polyvinyl pyrrolidone, and polyethylene oxide as a solute. The solution-like binder is more conducive to dispersion in the slurry, more effectively and evenly bonding the various components in the coating, thereby improving the mechanical properties of the composite diaphragm. Optionally or preferably, the binder is polystyrene butadiene rubber.

[0029] In a feasible embodiment, the thickener is sodium carboxymethyl cellulose, the dispersant is polyacrylamine, and the binder is polystyrene-butadiene rubber. The selection of such thickener, dispersant and binder can cooperate with each other to improve the mechanical properties of the composite diaphragm, and further improve the service life and safety performance of the composite diaphragm and the battery.

[0030] In a feasible embodiment, the solid electrolyte may be at least one selected from garnet-type solid electrolytes, sulfide solid electrolytes, NASICON-type solid electrolytes, LiPON-type electrolytes, and perovskite-type solid electrolytes. Optionally or preferably, the solid electrolyte may be NASICON-type. Such a solid electrolyte structure is porous, and it is easier to prepare a solid electrolyte with a higher specific surface area, which has a better liquid retention effect.

[0031] In a feasible embodiment, the solid electrolyte may also be a solid electrolyte with a high specific surface area prepared by a special method, such as a porous solid electrolyte prepared by electrospinning or a solid electrolyte with a high specific surface area achieved by doping or the like.

[0032] Accordingly, the present application also provides a method for preparing a composite membrane. The preparation method comprises the following steps:

[0033] S110, obtaining a basement membrane.

[0034] S120, adding a thickener into water and stirring evenly to obtain a first mixed solution.

[0035] In a feasible embodiment, the stirring rate of S120 is 1000-6000 rpm. Optionally or preferably, the stirring rate in step S120 is 1500-5000 rpm. Optionally or preferably, the stirring rate in step S120 is 1500-3000 rpm. Optionally or preferably, the stirring rate in step S120 is 1500-2500 rpm.

[0036] S130, adding a solid electrolyte to the first mixed solution obtained in S120, stirring evenly, to obtain a second mixed solution.

[0037] In a feasible implementation manner, the ratio of water to solid electrolyte in the second mixed solution is: (2-4):1.

[0038] In a feasible embodiment, the stirring rate of step S130 is 1000-6000 rpm. Optionally or preferably, the stirring rate in step S130 is 1500-5000 rpm. Optionally or preferably, the stirring rate in step S130 is 2000-4000 rpm. Optionally or preferably, the stirring rate in step S130 is 2000-3000 rpm.

[0039] S140, adding a hydrophobic agent and a dispersant to the second mixed solution obtained in S130, stirring evenly, to obtain a third mixed solution.

[0040] In a feasible embodiment, the stirring rate of S140 is 1000-6000 rpm. Optionally or preferably, the stirring rate in step S140 is 1500-5000 rpm. Optionally or preferably, the stirring rate in step S140 is 2000-4000 rpm. Optionally or preferably, the stirring rate in step S140 is 2000-3000 rpm.

[0041] S150, adding a binder to the third mixed solution obtained in S140, stirring evenly to obtain a target slurry.

[0042] The stirring rate of S130 is 1000-6000 rpm. Optionally or preferably, the stirring rate in step S150 is 1000-5000 rpm. Optionally or preferably, the stirring rate in step S150 is 1000-4000 rpm. Optionally or preferably, the stirring rate in step S150 is 1000-2000 rpm.

[0043] S160, coating the target slurry obtained in S150 onto at least one side of the base film to obtain a precursor composite diaphragm.

[0044] In a feasible embodiment, the coating method can be blade coating, roller coating, slit coating or spin coating.

[0045] S1170, solidifying the precursor membrane obtained in S160 to obtain a target composite membrane.

[0046] In a feasible implementation, the operation of curing the precursor membrane is drying and curing. The drying and curing temperature is 90° C. to 150° C., and the drying and curing time is 10 min to 60 min.

[0047] The preparation method of the composite diaphragm provided in the present application is not just a simple mixing of different raw materials, but an optimal preparation effect is achieved through orderly feeding steps. The flow is clear and the process is simple. The prepared composite diaphragm achieves the effect of high liquid retention rate and low moisture content. While having good mechanical properties, the battery prepared therefrom has good cycle life and safety performance, which is conducive to wide application.

[0048] Accordingly, an embodiment of the present application further provides a lithium battery comprising the composite diaphragm.

[0049] With reference to the above implementation contents, in order to make the technical solution of the present application more specific, clear and easy to understand, the technical solution of the present application is now exemplified. However, it should be noted that the contents to be protected by the present application are not limited to the following embodiments.

[0050] Example 1

[0051] Step 1: Add 4 grams of sodium carboxymethyl cellulose, a thickener, into 160 grams of pure water and dissolve and stir at 2000 rpm to obtain a first mixed solution;

[0052] Step 2: Convert 80g BET to 80m 2 / g, and a solid electrolyte of lithium aluminum titanium phosphate with a D50 of 5.5 μm is added to the first mixed solution obtained in step 1, and stirred and dispersed at 2500 rpm to obtain a second mixed solution;

[0053] Step 3: Add 3 grams of hydrophobic agent potassium methyl silicate and 5 grams of dispersant sodium hexametaphosphate to the second mixed solution obtained in step 2 and disperse evenly at 2300 rpm to obtain a third mixed solution;

[0054] Step 4: Add 8 grams of binder SBR (polystyrene butadiene rubber) emulsion to the third mixed solution obtained in step 3 and disperse evenly at 1500 rpm to obtain a target slurry;

[0055] Step 5: Apply the target slurry obtained in step 4 to one side of a 9 μm thick PE base film by blade coating, dry at 90° C. for 30 min, and solidify into a film to obtain a composite diaphragm.

[0056] Example 2

[0057] Step 1: Add 4 grams of sodium carboxymethyl cellulose, a thickener, into 340 grams of pure water and dissolve and stir at 2000 rpm to obtain a first mixed solution;

[0058] Step 2: Convert 85g BET to 80m 2 / g, and a solid electrolyte of lithium aluminum titanium phosphate with a D50 of 5.5 μm is added to the first mixed solution obtained in step 1, and stirred and dispersed at 2500 rpm to obtain a second mixed solution;

[0059] Step 3: Add 5 grams of hydrophobic agent potassium methyl silicate and 4 grams of dispersant sodium hexametaphosphate to the second mixed solution obtained in step 2 and disperse evenly at 2300 rpm to obtain a third mixed solution;

[0060] Step 4: Add 7 grams of binder SBR (polystyrene butadiene rubber) solution to the third mixed solution obtained in step 3 and disperse evenly at 1500 rpm to obtain a target slurry;

[0061] Step 5: Apply the target slurry obtained in step 4 to one side of a 9 μm thick PE base film by blade coating, dry at 90° C. for 30 min, and solidify into a film to obtain a composite diaphragm.

[0062] Example 3

[0063] Step 1: Add 5 grams of sodium carboxymethyl cellulose, a thickener, into 240 grams of pure water and dissolve and stir at 2000 rpm to obtain a first mixed solution;

[0064] Step 2: Convert 75g BET to 80m 2 / g, and a solid electrolyte of lithium aluminum titanium phosphate with a D50 of 8 μm is added to the first mixed solution obtained in step 1, and stirred and dispersed at 2500 rpm to obtain a second mixed solution;

[0065] Step 3: Add 5 grams of hydrophobic agent potassium methyl silicate and 4 grams of dispersant sodium hexametaphosphate to the second mixed solution obtained in step 2 and disperse evenly at 2300 rpm to obtain a third mixed solution;

[0066] Step 4: Add 6 grams of binder SBR (polystyrene butadiene rubber) solution to the third mixed solution obtained in step 3 and disperse evenly at 1500 rpm to obtain a target slurry;

[0067] Step 5: Apply the target slurry obtained in step 4 to one side of a 9 μm thick PE base film by blade coating, dry at 90° C. for 30 min, and solidify into a film to obtain a composite diaphragm.

[0068] Example 4

[0069] This embodiment is basically the same as Embodiment 3, except that, in this embodiment, the solid electrolyte is lithium lanthanum titanate, the hydrophobic agent is sodium methyl silicate, the dispersant is polyacrylamine, and the binder is polyvinylidene fluoride solution.

[0070] Example 5

[0071] This embodiment is basically the same as embodiment 4, except that the BET of the solid electrolyte lithium lanthanum titanium oxide in this embodiment is 20m 2 / g.

[0072] Example 6

[0073] This embodiment is basically the same as Embodiment 4, except that, in this embodiment, the D50 of the solid electrolyte lithium lanthanum titanium oxide is 0.3 μm.

[0074] Example 7

[0075] This embodiment is basically the same as Embodiment 1, except that the base film in this embodiment is a PP base film.

[0076] Example 8

[0077] This embodiment is basically the same as Embodiment 1, except that the coating thickness in this embodiment is 5 μm.

[0078] Example 9

[0079] Step 1: Add 4 grams of thickener sucrose into 88 grams of pure water and dissolve at 2100 rpm and stir to disperse evenly to obtain a first mixed solution;

[0080] Step 2: Convert 79g BET to 55m 2 / g, D50 of 6.1 μm, and lithium germanium aluminum phosphate, a solid electrolyte, is added to the first mixed solution obtained in step 1, and stirred and dispersed at 2700 rpm to obtain a second mixed solution;

[0081] Step 3: Add 5 grams of hydrophobic agent sodium methyl silicate and 4 grams of dispersant polyacrylamine to the second mixed solution obtained in step 2 and disperse evenly at 2400 rpm to obtain a third mixed solution;

[0082] Step 4: Add 5 g of the binder polyvinylidene fluoride solution to the third mixed solution obtained in step 3 and disperse evenly at 2500 rpm to obtain a target slurry;

[0083] Step 5: The target slurry obtained in step 4 is coated on one side of a 12 μm thick PE base film by knife coating, and dried at 85° C. for 40 min to form a film to obtain a composite diaphragm.

[0084] Example 10

[0085] Step 1: Add 4 grams of sodium carboxymethyl cellulose, a thickener, into 88 grams of pure water and dissolve and stir at 2000 rpm to obtain a first mixed solution;

[0086] Step 2: Convert 75g BET to 55m 2 / g, and a solid electrolyte lithium lanthanum titanate with a D50 of 6.1 μm is added to the first mixed solution obtained in step 1, and stirred and dispersed at 3000 rpm to obtain a second mixed solution;

[0087] Step 3: Add 5 grams of hydrophobic agent sodium methyl silicate and 4 grams of dispersant polyacrylamine to the second mixed solution obtained in step 2 and disperse them evenly at 2300 rpm to obtain a third mixed solution;

[0088] Step 4: Add 6 grams of the binder polyvinylidene fluoride solution to the third mixed solution obtained in step 3 and disperse evenly at 1500 rpm to obtain the target slurry;

[0089] Step 5: The target slurry obtained in step 4 is coated on one side of a 12 μm thick PE base film by blade coating, and dried at 90° C. for 30 min to form a film, thereby obtaining a composite diaphragm.

[0090] Comparative Example 1

[0091] Step 1: Add 4 grams of sodium carboxymethyl cellulose to 160 grams of pure water and dissolve at 2000 rpm and stir thoroughly to disperse evenly;

[0092] Step 2: 80 grams of BET is 80m 2 / g, lithium aluminum titanium phosphate with a D50 of 5.5 μm is added to the solution in step 1 and stirred at 2500 rpm to be evenly dispersed;

[0093] Step 3: Add 5 g of sodium hexametaphosphate to the slurry in step 2 and disperse evenly at 2300 rpm;

[0094] Step 4: Add 8 grams of SBR solution to the slurry in step 3 and disperse evenly at 1500 rpm;

[0095] Step 5: Apply the slurry obtained in step 4 to one side of a 9 μm thick PE base film by knife coating, dry at 90° C. for 30 min, and solidify into a film.

[0096] Comparative Example 2

[0097] Step 1: Add 4 grams of sodium carboxymethyl cellulose to 80 grams of pure water and dissolve at 2000 rpm and stir thoroughly to disperse evenly;

[0098] Step 2: 80g of BET is 10m 2 / g, lithium aluminum titanium phosphate with a D50 of 5.5 μm is added to the solution in step 1 and stirred at 2500 rpm to be evenly dispersed;

[0099] Step 3: Add 3 grams of potassium methyl silicate and 5 grams of sodium hexametaphosphate to the slurry in step 2 and disperse evenly at 2300 rpm;

[0100] Step 4: Add 8 grams of SBR solution to the slurry in step 3 and disperse evenly at 1500 rpm;

[0101] Step 5: Apply the slurry obtained in step 4 to one side of a 9 μm thick PE base film by knife coating, dry at 90° C. for 30 min, and solidify into a film.

[0102] Comparative Example 3

[0103] Step 1: Mix 4 grams of sodium carboxymethyl cellulose and 80 grams of BET 80m 2 / g, lithium aluminum titanium phosphate with a D50 of 5.5 μm, 5 g of sodium hexametaphosphate and 8 g of SBR solution were added to 80 g of pure water and dissolved at 2000 rpm and stirred thoroughly to disperse evenly;

[0104] Step 2: The slurry obtained in step 1 is coated on one side of a 9 μm thick PE base film by knife coating, and dried at 90° C. for 30 min to form a film.

[0105] Performance Testing

[0106] (1) Hydrophobicity test

[0107] Drop the electrolyte on the surface of the material and compare the contact angle of the electrolyte on the surface of the material. The larger the contact angle, the stronger the hydrophobicity of the material.

[0108] (2) Liquid retention rate test

[0109] Take a piece of dry diaphragm and weigh it as M1. After soaking it in electrolyte for 30 minutes, use filter paper to gently absorb the electrolyte on the membrane surface and weigh it as M2. The liquid retention rate = (M2-M1) / M1*100%;

[0110] (3) Moisture test

[0111] Test using a coulometric moisture meter;

[0112] (4) Mechanical properties test

[0113] Puncture strength: The electronic tensile testing machine is used to test the puncture resistance of the battery separator;

[0114] (5) Battery performance test: a button-type lithium-ion battery was composed of an NCM523 positive electrode sheet, a metal lithium negative electrode sheet and the composite separator prepared above. The battery prepared above was subjected to a battery charge and discharge capacity cycle test at 25°C.

[0115] The performance test results are shown in Table 1.

[0116] Figure 1 : is a comparison chart of the hydrophobicity of the diaphragms prepared in Example 1 and Comparative Example 1 of the present application. Figure 1 It can be seen that the hydrophobicity of the composite diaphragm prepared in Example 1 of the present application is greatly improved compared with the diaphragm prepared in Comparative Example 1, and the electrolyte adsorption effect is also significantly improved.

[0117] Table 1: Performance test results of composite diaphragms of examples and comparative examples

[0118]

[0119]

[0120]

[0121] As can be seen from Table 1, the composite diaphragm provided in the embodiment of the present application has a higher liquid retention rate, moisture content and puncture strength, and the mechanical properties are significantly improved compared to the solid electrolyte diaphragm without hydrophobic agent and low specific surface area. Higher mechanical strength can reduce the probability of internal short circuit of lithium batteries under poor working conditions, thereby greatly improving the safety of lithium batteries. At the same time, the first charge and discharge efficiency of the composite diaphragm provided in the embodiment of the present application is significantly improved compared with the comparative example, and the 100-week capacity retention rate is also greatly improved. It can be seen that the lithium battery prepared by the composite diaphragm provided by the present application has a good cycle life.

[0122] In addition, from the above experimental results, it can be seen that the mechanical properties, charge and discharge efficiency and 100-week capacity retention rate of the battery diaphragm prepared in Example 2 of the present application are better than those in other embodiments. It can be seen that the ratio between the solid electrolyte, thickener, hydrophobic agent, dispersant and binder of the composite diaphragm prepared in this way and the preparation conditions are better, and the prepared composite diaphragm has better performance.

[0123] The basic concepts have been described above. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of this specification. Although not explicitly stated here, those skilled in the art may make various modifications, improvements and corrections to this specification. Such modifications, improvements and corrections are suggested in this specification, so such modifications, improvements and corrections still belong to the spirit and scope of the exemplary embodiments of this specification.

[0124] At the same time, this specification uses specific words to describe the embodiments of this specification. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of this specification. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different positions in this specification does not necessarily refer to the same embodiment. In addition, certain features, structures or characteristics in one or more embodiments of this specification can be appropriately combined.

[0125] In addition, unless explicitly stated in the claims, the order of the processing elements and sequences described in this specification, the use of alphanumeric characters, or the use of other names are not intended to limit the order of the processes and methods of this specification. Although the above disclosure discusses some invention embodiments that are currently considered useful through various examples, it should be understood that such details are only for illustrative purposes, and the attached claims are not limited to the disclosed embodiments. On the contrary, the claims are intended to cover all modifications and equivalent combinations that are consistent with the essence and scope of the embodiments of this specification.

[0126] Similarly, it should be noted that in order to simplify the description disclosed in this specification and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this specification, multiple features are sometimes combined into one embodiment, figure or description thereof. However, this disclosure method does not mean that the features required by the subject matter of this specification are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.

[0127] In some embodiments, numbers describing the number of components and attributes are used. It should be understood that such numbers used in the description of the embodiments are modified by the modifiers "about", "approximately" or "substantially" in some examples. Unless otherwise specified, "about", "approximately" or "substantially" indicate that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used in the specification and claims are approximate values, which may change according to the required features of individual embodiments. In some embodiments, the numerical parameters should take into account the specified significant digits and adopt the general method of retaining digits. Although the numerical domains and parameters used to confirm the breadth of their range in some embodiments of this specification are approximate values, in specific embodiments, the setting of such numerical values ​​is as accurate as possible within the feasible range.

[0128] Each patent, patent application, patent application publication, and other materials, such as articles, books, specifications, publications, documents, etc., cited in this specification are hereby incorporated by reference in their entirety. Except for application history documents that are inconsistent with or conflicting with the contents of this specification, documents that limit the broadest scope of the claims of this specification (currently or later attached to this specification) are also excluded. It should be noted that if the descriptions, definitions, and / or use of terms in the materials attached to this specification are inconsistent or conflicting with the contents described in this specification, the descriptions, definitions, and / or use of terms in this specification shall prevail.

[0129] Finally, it should be understood that the embodiments described in this specification are only used to illustrate the principles of the embodiments of this specification. Other variations may also fall within the scope of this specification. Therefore, as an example and not a limitation, alternative configurations of the embodiments of this specification may be considered consistent with the teachings of this specification. Accordingly, the embodiments of this specification are not limited to the embodiments explicitly introduced and described in this specification.

Claims

1. A composite diaphragm, characterized in that: The composite diaphragm comprises: Basement membrane; A coating, the coating being disposed on at least one side of the base film in a thickness direction, the coating comprising a solid electrolyte, a thickener, a hydrophobic agent, a dispersant and a binder; The specific surface area of ​​the solid electrolyte is 20 m 2 / g~100m 2 / g, the hydrophobic agent is selected from at least one of sodium methyl silicate and potassium methyl silicate.

2. The composite diaphragm according to claim 1, characterized in that: The mass ratio of the solid electrolyte, thickener, hydrophobic agent, dispersant and binder in the coating is (75-85): (1-8): (1-5): (1-8): (1-10).

3. The composite diaphragm according to claim 1, characterized in that: The particle size D50 of the solid electrolyte is 0.3-8 μm, the thickness of the base film is 1-15 μm, and the thickness of the coating is 1-10 μm.

4. The composite diaphragm according to claim 1, characterized in that: The thickener is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, sodium carboxymethyl cellulose, methyl cellulose and sucrose.

5. The composite diaphragm according to claim 1, characterized in that: The dispersant is selected from one or more of sodium silicate, sodium hexametaphosphate, sodium stearate, fatty alcohol polyoxyethylene ether, polyacrylamine and polyvinyl alcohol.

6. The composite diaphragm according to claim 1, characterized in that: The binder is selected from one or more of the emulsions or solutions with polystyrene-butadiene rubber, vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polymethyl methacrylate, polyacrylonitrile, polyimide, polyvinyl pyrrolidone, and polyethylene oxide as solutes.

7. A method for preparing a composite diaphragm, characterized in that: The preparation method comprises the following steps: Obtain basement membrane, Adding the thickener into water and stirring evenly to obtain a first mixed solution; Adding a solid electrolyte to the first mixed solution and stirring evenly to obtain a second mixed solution; Adding a hydrophobic agent and a dispersant to the second mixed liquid, stirring evenly, to obtain a third mixed liquid; Adding a binder to the third mixed liquid and stirring evenly to obtain a target slurry, Applying the target slurry to at least one side of the base film to obtain a precursor composite diaphragm; The precursor membrane is solidified to obtain a target composite membrane.

8. The preparation method according to claim 7, characterized in that: The ratio of water in the second mixed solution to the solid electrolyte is: (2-4):

1.

9. The preparation method according to claim 7, characterized in that: The operation of curing the precursor membrane is drying and curing, the drying and curing temperature is 90-150° C., and the drying and curing time is 10-60 min.

10. A lithium battery, characterized in that: It comprises the composite diaphragm as claimed in any one of claims 1 to 6.